A novel approach for artificially generating horizontal wind gusts based on a movable plate: The Paddle. Issue 230 (November 2022) - Wood, J.N.; Breuer, M.; Neumann, T.
Abstract: The paper is concerned with a novel approach to generate horizontal wind gusts in classical wind tunnels. Assuming an open test section of an Eiffel- or Göttingen-type wind tunnel, the new wind gust generator denoted "The Paddle" can be easily retrofitted to such experimental setups at low costs. The device is constructed based on commercially available components including a programmable software tool that allows to adjust all relevant kinematic parameters. Five predefined motion patterns of the paddle are investigated which differ according to the achieved blocking ratio of the wind tunnel nozzle as well as the velocity and acceleration of the downward and upward motion of the paddle . It is shown that the shape and intensity of the generated gusts can be fully controlled by these parameters. That guarantees a strong individual adjustability and customization of the induced gusts. Furthermore, a synchronization of the wind gust generator with measurement devices such as laser-Doppler anemometer or particle-image velocimetry is easy to implement. An extensive measurement campaign has shown that the generated horizontal gusts are highly reproducible for the presently investigated laminar boundary layer and vary in the core area of the gust measurements solely according to free-stream turbulence of the wind tunnel. Highlights: New type of retrofittable wind gust generator (WGG) denoted the paddle. A novel approach for artificially generating wind gusts in a wind tunnel. Generation of horizontal wind gusts with large gust ratios GR > 1. Individual adjustability and customization of the gust shapes. Possibility to generate a complex sequence of differently shaped gusts.